Increased motor performance and responsivity in physical fitness after high-intensity functional training in excess weight adolescents - Frederico Bento de Moraes Junior; Maiara Cristina Tadiotto; Patricia Ribeiro Paes Corazza; Francisco Jose de Menezes-Junior; Neiva Leite (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Motor competence (MC) is essential for motor development and an active lifestyle. However, adolescents with excess weight face challenges like low physical fitness and cardiometabolic alterations that affect MC. While high-intensity functional training (HIFT) improves physical fitness and reduces cardiometabolic risks, its effects on MC remain underexplored. Objective: This study aimed to investigate the impact of different types of physical training on motor competence and physical fitness in excess weight adolescents. Methodology: The sample had 46 adolescents of both sexes, aged 10 to 16 years, distributed into HIFT(n=10), high-intensity interval training (HIIT, n=12), moderate-intensity continuous training (MICT, n=12), and control group (CG, n=12). Anthropometric measurements, body composition, physical fitness, and motor competence with supine-to-stand time (STSTIME) were assessed before and after the intervention. Repeated measures ANOVA, effect size, and prevalence of respondents were used for statistical analysis. Results: HIFT had a decrease in BMI (p=0.04), WHtR (p=0.050), and %FM (p<0.001), an increase in %FFM (p<0.001), ABD strength (p<0.01), and flexibility (p<0.03), and very beneficial improvement in STSTIME (p< 0.001) in relation to the other groups. On the other hand, HIIT (p<0.003) and MICT (p<0.02) had greater handgrip strength than HIFT. Furthermore, higher frequencies of HIFT respondents had a decrease in BMI and %FM and an increase in %FFM (p<0.05), flexibility, and STSTIME in relation to the other groups (p=0.001). Conclusions: HIFT was significantly more effective than the other protocols in improving body composition, abdominal strength, flexibility, and floor rise time.